One-session mindfulness meditation interventions - Brazão, Vasco de Almeida Esteves Cavaleiro (2019)
Mindfulness has enjoyed increasing popularity among Western scholars and practitioners, leading to a surge of scientific publications. Within this field, more and more studies employ an experimental approach and focus on the immediate effects of one session of mindfulness meditation. This dissertation sought to contribute to this subfield in three ways. To make a general survey of the field, a preliminary systematic scoping of onesession mindfulness meditation studies was conducted. The results of this review, presented in Chapter 2, allowed us to characterize and critically evaluate the typical study in this field. One important contribution of this thesis is the raw data (a table of coded studies) for the scoping review, accessible online at https://osf.io/h7k9g/. Chapter 3 presents a preregistered (https://aspredicted.org/blind.php?x=dn7uz3) experimental study comparing the effects of mindfulness meditation to a mindwandering control induction on aggression. Several important limitations constrained our ability to draw inferences from this study, and they are examined in the detail in the chapter. Chapter 4 consolidates the main contribution of this thesis by reflecting on the previous work and detailing a list of recommendations for future researchers in this subfield. This is done with particular attention to methodological and theoretical issues raised as a result of psychology’s “replication crisis”.